Toothed whale auditory brainstem responses measured with a non-invasive, on-animal tag - Smith, Adam B.; Madsen, Peter T.; Johnson, Mark; Tyack, Peter; Wahlberg, Magnus (JASA Express Letters, 2021)
This work was funded by Grant No. N00014-20-1-2748 from the United States Office of Naval Research (ONR) awarded to M.W. Tag development was supported by ONR Grant Nos. N00014-16-1-2852, N00014-18-1-2062, and N00014-20-1-2709. M.J. was supported by the Aarhus University Research Foundation and the EU H2020 research and innovation program under Marie Skłodowska-Curie Grant No. 754513. Empirical measurements of odontocete hearing are limited to captive individuals, constituting a fraction of species across the suborder. Data from more species could be available if such measurements were collected from unrestrained animals in the wild. This study investigated whether electrophysiological hearing data could be recorded from a trained harbor porpoise (Phocoena phocoena) using a non-invasive, animal-attached tag. The results demonstrate that auditory brainstem responses to external and self-generated stimuli can be measured from a stationary odontocete using an animal-attached recorder. With additional development, tag-based electrophysiological platforms may facilitate the collection of hearing data from freely swimming odontocetes in the wild. Peer reviewed